Comparative Study of Open versus Closed Lateral Sphincterotomy for the Management of Anal Fissure - Khalid Mehmood Nizami, Fatima Ahmad, Muhammad Faraz Khalid, Sumaira Hassan, Javed Ahmed, Muhammad Haseeb Amjad (Pakistan Journal of Medical & Health Sciences, 2025)
Background:Anal fissure is a common ailment. Most fissures heal spontaneously but some go into chronicityand surgery must be resorted to for these obstinate cases. Lateral internal sphincterotomy, which entails partial division of the internal anal sphincter is currently the treatment of choice for such cases. This procedure can be performed through different techniques. Objective: To see whether a closed approach to lateral internal sphincterotomy is better than the open one regardingefficacy and lower complication rate. Methodology: This prospective study was carried out at Outpatient Department of Surgery, Avicenna Hospital Lahore from 1st October 2022 to 30th September 2023. A total of 64 patients, selected and they s were divided into two groups by purposive consecutive sampling. Results: Both techniques were equally effective in relieving symptoms and speeding up the healing process. The post-operative recovery was pain free, shorter, and less complicated with closed sphincterotomy. Conclusion:The closed technique may be a bettertreatment choice for chronic anal fissure because of better postoperative recovery. Keywords: Anal fissure, Chronic fissure, lateral sphincterotomy, Internal sphincterotomy, Closed sphincterotomy